2012
DOI: 10.1161/strokeaha.111.645614
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in Cognitive Function and Brain Connectivity in Severe Asymptomatic Carotid Stenosis

Abstract: Background and Purpose-Severe asymptomatic carotid stenosis has been associated with cognitive impairment, but it is unknown whether this association is attributable to effects on brain connectivity. We present cognitive network abnormalities in a group of patients at a presymptomatic stage. Methods-Seventeen patients with Ն70% asymptomatic stenosis of unilateral internal carotid artery were compared with 26 healthy controls utilizing a comprehensive neuropsychological battery, the dizziness handicap inventory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
118
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(136 citation statements)
references
References 44 publications
11
118
0
6
Order By: Relevance
“…3 Detecting microstructural changes due to chronic ischemia potentially enables early identification of patients at risk of cognitive impairment. 3,20 However, detecting microstructural changes has been hampered by the limited sensitivity of DTI in fiber-crossing areas. 7 In this study, DKI demonstrated microstructural changes, predominantly in the dorsal part of the deep white matter, where conventional MR imaging frequently demonstrates ischemic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…3 Detecting microstructural changes due to chronic ischemia potentially enables early identification of patients at risk of cognitive impairment. 3,20 However, detecting microstructural changes has been hampered by the limited sensitivity of DTI in fiber-crossing areas. 7 In this study, DKI demonstrated microstructural changes, predominantly in the dorsal part of the deep white matter, where conventional MR imaging frequently demonstrates ischemic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…For DTI, voxelwise fractional anisotropy (FA) was analyzed after applying preprocessing with Tract-Based Spatial Statistics from the FMRIB Software Library (TBSS; http://fsl.fmrib.ox.ac.uk/fsl/fslwiki/TBSS), as previously described. 12 We performed a paired t test for withingroup interval changes of the FA maps and then a 2-sample t test for between-group comparison of the interval changes with a significance set at P Ͻ .05 with family-wise error rate correction for multiple comparisons (random permutations, n ϭ 5000).…”
Section: Mr Imaging Processing and Analysismentioning
confidence: 99%
“…10,11 We previously demonstrated that patients with unilateral asymptomatic carotid stenosis of Ն70% had more dizziness/ unsteadiness and poorer verbal memory, executive function, and visuospatial perception than the healthy controls, accompanied by extensive widespread disruption of long-range structural and functional connectivity. 12,13 The mechanisms are likely attributed to microemboli from unstable carotid plaques 5 and/or chronic hypoperfusion. 14,15 Single-arm studies of carotid revascularization accomplished by either carotid endarterectomy or CAS reported the controversial results of cognitive enhancement in patients with asymptomatic carotid stenosis.…”
mentioning
confidence: 99%
“…11,12 With regard to largescale networks, changes in white matter microstructure and RSFC may account for cognitive decline in these patients. 13 In neurodegenerative diseases, impaired cerebral hemodynamics indicate lower capacity to modulate resistance of cerebral vessels because of cerebral atrophy. 14 Recently, associations between cerebral hemodynamics and white matter hyperintensities have also been reported in older adults without extracranial artery stenoses.…”
Section: Introductionmentioning
confidence: 99%